Analisis Tafsir Lintas Budaya Serat Suluk Samariyah atas Yohanes 4:4-42 - Robby Igusti Chandra (Jurnal EFATA: Jurnal Teologi dan Pelayanan, 2020)
Interpretation or analysis of John 4:5-42 is numerous. However, perhaps a few works are done to analyze the interpretation done in different cultures and faith contexts, especially in Java. One of them is Serat Suluk Pawestri Samariyah that was written in 1921 in central Java. This article explores this Christian Kejawen or local spirituality text to understand the nuances and concepts underlying the text to enrich future contextualization and cross-cultural hermeneutic process. The approach of the study is the narrative interpretation method for both the Serat Suluk Pawestri Samariyah and John 4:4-42 to uncover the similarities, differences, and local concepts. As the result, it is found that in both texts Christ is narrated as He who took initiative to approach the Samaritan woman and to offer God’s grace. However, after someone receives the grace of the Living Water or Salvation, on the one side, Serat Suluk Pawestri Samariyah gives a holistic and practical way to conduct his or her life. Yet, on the other side, the text gives the impression that it teaches a dualistic view.AbstrakKarya tafsiran dan telaah atas Yohanes 4:5-42 sangat kaya. Namun, bagaimana budaya yang dan kepercayaan yang berbeda menafsirkannya mungkin belum banyak digarap, khususnya untuk Indonesia. Salah satu karya adalah Serat Suluk Pawestri Samariyah yang ditulis di tahun 1921 di Jawa Tengah. Artikel ini menelusuri karya sastra Kejawen Kristiani ini untuk menangkap nuansa-nuansa serta konsep yang memperlengkapi proses kontekstualisasi dan hermeneutik lintas budaya. Pendekatan yang digunakan adalah tafsir narasi baik terhadap Serat Suluk Pawestri Samariyah dan Injil Yohanes 4:4-42 sehingga dapat digali kesamaan, perbedaan, dan konsep-konsep budaya lokal. Sebagai hasilnya, didapatkan bahwa, konsep Kristus sebagai sosok yang berprakarsa mendekati sang wanita Samaria dan menawarkan anugerah Tuhan sangat nyata dalam kedua teks, namun pemahaman teks lokal ini mengenai konsekuensi mengenai hidup sesudah menerima air hidup yaitu pengampuan dan keselamatan terkesan sangat dualistis walaupun, sangat utuh dalam pedoman menjalani hidup baru.